Hubungan Alat Pelindung Diri dan Personal Hygine terhadap Gejala Dermatitis pada Pekerja Tambak di Desa Seuneubok Aceh Kabupaten Aceh Tamiang - Vivi Indah Sari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Dermatitis is a common skin disease that can be influenced by various internal and external factors. According to the Puskesmas Sungai Iyu report for 2023-2024, there were 180 cases of dermatitis. This study aims to analyze the factors associated with dermatitis symptoms among shrimp pond workers in Seneubok Aceh Village, Bendahara District, Aceh Tamiang Regency. The independent variables studied include contact duration, years of employment, personal hygiene, and the use of Personal Protective Equipment (PPE), while the dependent variable is dermatitis symptoms, including itching, redness, and rashes. The method used was a correlational analytic study with a cross-sectional design, involving 54 respondents from a total of 112 shrimp pond workers in the village as samples. The population in this study consists of all shrimp pond workers in Seneubok Aceh Village, Bendahara District, Aceh Tamiang Regency. The results show that there is no significant relationship between the use of PPE (p-value = 0.047) and personal hygiene (p-value = 0.002) with dermatitis symptoms. In conclusion, factors associated with dermatitis symptoms in shrimp pond workers are personal hygiene, and the use of PPE. It is recommended that shrimp pond workers increase the use of PPE, practice good personal hygiene, and limit the duration of contact with pond water to reduce the risk of dermatitis.